Analisis Preferensi Konsumen Dalam Memilih Coffee Shop di Kota Padangsidimpuan - Arpan Dalimunthe; Retna Astuti Kuswardani; Siswa Panjang Hernosa (Jayapangus Press, 2025)
Coffee Shop business is considered very promising with various characteristics that exist at this time. The purpose of this study is to determine the characteristics of coffee shop respondents, attributes and levels of coffee shops, the order of coffee shop attributes in Padangsidimpuan City. The data used in this study are primary data and secondary data, the sample in this study amounted to 100 respondents with the judgment sampling method. The data analysis method used is using conjoint analysis. For the order of coffee shop attributes are location, price, coffee shop atmosphere, coffee shop service, products and facilities. This shows that the attribute considered most important by consumers in choosing a Coffee Shop in Padangsidimpuan City is the location attribute. The results of the Pearson's R and Kendall's tests show significant results between consumer preferences in choosing a Coffee Shop in Padangsidimpuan City. It is necessary to understand the characteristics of respondents, so that coffee shops will be able to make more appropriate decisions about marketing strategies, determine products and atmospheres to increase respondent satisfaction and increase sales. The attributes and levels of coffee shops in Padangsidimpuan are: Location close to residence, Prices of Rp. 16,000 – Rp. 25,000, outdoor coffee shop atmosphere, responsive coffee shop service, attractive product displays and wifi facilities so that by understanding these consumer preferences, coffee shops can increase satisfaction and increase sales by meeting consumer needs and expectations.